2003
DOI: 10.1038/sj.leu.2402699
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of nm23-H1 proteins expressed on cell surface in non-Hodgkin's lymphoma

Abstract: The nm23 gene was isolated as a metastasis suppressor gene that exhibits low expression in high-level metastatic cancer cells. Its gene is related to the prognosis of acute myelogenous leukemia (AML) and non-Hodgkin's lymphoma (NHL). In this study, we examined the expression of nm23-H1 protein on the lymphoma cell surface of NHL. In 28 of 108 cases (25.9%), we observed Ն20% of cell surface nm23-H1 protein expression and expression was especially high in peripheral T cell lymphomas and extranodal NK/T cell lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…3 We previously reported that the nm23-H1 protein was strongly expressed on the surface of neoplastic cells of PTCL and extranodal NK/T-cell lymphomas, 4 and we also observed a significant correlation between the serum nm23-H1 level and the degree of its cell surface expression. This suggested that the serum nm23-H1 level reflects the proliferation rate of lymphoma cells, and that, in PTCL and NK-NHL, large amounts of nm23-H1 molecules are secreted from the neoplastic cells.…”
Section: Figuresupporting
confidence: 59%
“…3 We previously reported that the nm23-H1 protein was strongly expressed on the surface of neoplastic cells of PTCL and extranodal NK/T-cell lymphomas, 4 and we also observed a significant correlation between the serum nm23-H1 level and the degree of its cell surface expression. This suggested that the serum nm23-H1 level reflects the proliferation rate of lymphoma cells, and that, in PTCL and NK-NHL, large amounts of nm23-H1 molecules are secreted from the neoplastic cells.…”
Section: Figuresupporting
confidence: 59%
“…Cell surface Nm23-H1 has been previously observed on NHL cells (18) and some myeloid cell lines (10,19). However, to our knowledge, this is the first time that binding of Nm23-H1 to AML cells from an exogenous soluble pool of protein, commensurate with that found in AML patients, has been shown.…”
Section: Discussionmentioning
confidence: 73%
“…In one study in non-Hodgkin's lymphoma (NHL), more than 20% of cells were positive for Nm23-H1 cell surface expression in more than 25% of cases (18). The authors went on to show that NHL patients with high Nm23-H1 cell surface expression had significantly reduced survival rates.…”
Section: Introductionmentioning
confidence: 99%
“…In a multi-institutional study involving a large number of patients, we found that serum nm23-H1 was an important and independent prognostic factor for patients with DLBCL and with peripheral T-cell lymphoma (9). Although there were still several unknowns, including the question of whether serum nm23-H1 is produced by lymphoma cells directly, and whether there is a correlation between serum nm23-H1 and intracellular nm23-H1 expression by the tumor cells, our subsequent studies (10,11) indicated that these factors are possible. In the present study, we, therefore, evaluated intracellular nm23-H1 protein expression using immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%